Standardization of Clinic Flow to Improve Patient Experience in a Student-Run Free Clinic - Neal Modi; Pranav Nandan (Journal of Student-Run Clinics, 2024)
The Saint Louis University Health Resource Center, a student-run free clinic, has seen a rapid expansion in both the number of services supplied by the clinic and the number of patients seen at clinic. While we are excited to serve more patients, the increase in volume has resulted in increased wait times and clinic throughput, the most frequent complaint of patients. To combat these growing concerns, we standardized the route patients take through the services the clinic provides and embedded this flow into a new statusboard that automatically logs the amount of time patients spend with each service and in the clinic overall. This information feeds directly into a process map of the clinic that better visualizes clinic processes. The utilization of a standardized statusboard resulted in a significant 12 minute and 44 second reduction in the median time patients spend in clinic and identified key decision points where bottlenecks occur in clinic flow. It also resulted in a statistically significant improvement in patent satisfaction. Our results demonstrate that standardizing clinic flow via an automated statusboard improves clinic efficiency, reduces throughput time, and can also significantly improve patient satisfaction. The resulting process map can also identify areas needing intervention and opportunities to continue expanding. As we continue to gather data on where clinic patients are spending the most time, we will continue to optimize services to provide the best experience possible for our patients.